Association between ambient PM2.5 and outpatient visits of children's respiratory diseases in a megacity in Central China - Liu, Le; Wang, Bingya; Qian, Nana; Wei, Huiyan; Yang, Guangmei; Wan, Leping; He, Yan (Frontiers in Public Health, 2022)
Objective To explore the relationship between ambient PM2.5 level and outpatient visits of children with respiratory diseases in a megacity, Zhengzhou, in central China. Methods We collected daily outpatient visit data, air pollutant data, and meteorological data at the monitoring points of Zhengzhou from the time period 2018 to 2020 and used Spearman's rank correlation to analyze the correlation between children's respiratory outpatient visits and air pollutants and meteorological factors. Generalized additive models were used to analyze the association between PM2.5 exposures and children's respiratory outpatient visits. A stratified analysis was further carried out for the seasons. Results From 2018 to 2020, the total number of outpatients with children's respiratory diseases was 79,1107, and the annual average concentrations of PM2.5, PM10, SO2, NO2, CO, and O3-8h in Zhengzhou were respectively 59.48 μg/m3, 111.12 μg/m3, 11.10 μg/m3, 47.77 μg/m3, 0.90 mg/m3 and 108.81 μg/m3. The single-pollutant model showed that the risk of outpatient visits for children with respiratory disease increased by 0.341% (95%CI: 0.274–0.407%), 0.532% (95%CI: 0.455–0.609%) and 0.233% (95%CI: 0.177–0.289%) for every 10 μg/m3 increase in PM2.5 with a 3-day lag, 1-day lag, and 1-day lag respectively for the whole year, heating period, and non-heating period. The multi-pollutant model showed that the risk of PM2.5 on children's respiratory disease visits was robust. The excess risk of PM2.5 on children's respiratory disease visits increased by 0.220% (95%CI: 0.147–0.294%) when SO2 was adjusted. However, the PM2.5 effects were stronger during the heating period than during the non-heating period. Conclusion The short-term exposure to PM2.5 was significantly associated with outpatient visits for children's respiratory diseases. It is therefore necessary to strengthen the control of air pollution so as to protect children's health.